2014
DOI: 10.1002/aic.14459
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of flow regimes in three‐dimensional confined impinging jets reactor

Abstract: Dynamic behaviors in a three‐dimensional confined impinging jets reactor (CIJR) were experimentally studied by a flow visualization technique at 100 ≤ Re ≤ 2000 and 2 ≤ D/d ≤ 12 (where D is the reactor diameter and d is the nozzle diameter). The effects of inlet Reynolds numbers (Re) and geometry configurations of the CIJR on the flow regimes have been investigated by a particle image velocimetry and a high‐speed camera. Results show that with the increasing Re, a segregated flow regime, a radial deflective os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
0
20
0
1
Order By: Relevance
“…At Re = 150, the deflective oscillation nearly keeps invariable and is not affected by the excitation of k < 20%. It should be noted that the induced deflective oscillation at Re ≤ 100 is distinct to the self‐sustained deflective oscillation at Re = 150, as the former is mainly induced by the axial oscillation which is caused by the excitation of the pulsed inflow, but the latter is mainly determined by the interaction of the impingement plane and the confined wall of chamber . Results in this study prove that the axial oscillation is caused by the inflow fluctuation in the opposed jets in CIJR while the deflective oscillation is a kind of self‐sustained oscillation …”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…At Re = 150, the deflective oscillation nearly keeps invariable and is not affected by the excitation of k < 20%. It should be noted that the induced deflective oscillation at Re ≤ 100 is distinct to the self‐sustained deflective oscillation at Re = 150, as the former is mainly induced by the axial oscillation which is caused by the excitation of the pulsed inflow, but the latter is mainly determined by the interaction of the impingement plane and the confined wall of chamber . Results in this study prove that the axial oscillation is caused by the inflow fluctuation in the opposed jets in CIJR while the deflective oscillation is a kind of self‐sustained oscillation …”
Section: Discussionmentioning
confidence: 54%
“…The recorded digital images were analyzed by the NIH image freeware to obtain the oscillation frequencies or oscillation amplitudes of the dynamic behavior of the impingement plane in CIJR. The detailed method of the image processing can be found in our previous papers …”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results in the literature have indicated that for Re≤100 a segregated steady flow regime occurs and at higher Reynolds numbers the flow is observed to transform to a dynamic chaotic flow regime in CIJR (Tucker and Suh, 1980;Mahajan and Kirwan, 1996;Johnson and Wood, 2000;Santos et al, 2005Santos et al, , 2008Santos et al, , 2009Li et al, 2014). Up to now the flow regime in CIJR has been intensively investigated, but the internal relationship between the oscillation behaviors and mixing performance has not been clearly revealed yet.…”
Section: Introductionmentioning
confidence: 87%